Dimethylarginine dimethylaminohydrolase-2 deficiency promotes vascular regeneration and attenuates pathological angiogenesis. (June 2016) - Lange, Clemens; Mowat, Freya; Sayed, Haroon; Mehad, Manjit; Duluc, Lucie; Piper, Sophie; Luhmann, Ulrich; Nandi, Manasi; Kelly, Peter; Smith, Alexander; Ali, Robin; Leiper, James; et al.
Abstract: Ischemia-induced angiogenesis is critical for tissue repair, but aberrant neovascularization in the retina causes severe sight impairment. Nitric oxide (NO) has been implicated in neovascular eye disease because of its pro-angiogenic properties in the retina. Nitric oxide production is inhibited endogenously by asymmetric dimethylarginines (ADMA and L-NMMA) which are metabolized by dimethylarginine dimethylaminohydrolase (DDAH) 1 and 2. The aim of this study was to determine the roles of DDAH1, DDAH2, ADMA and L-NMMA in retinal ischemia-induced angiogenesis. First, DDAH1, DDAH2, ADMA and L-NMMA levels were determined in adult C57BL/6J mice. The results obtained revealed that DDAH1 was twofold increased in the retina compared to the brain and the choroid. DDAH2 expression was approximately 150 fold greater in retinal and 70 fold greater in choroidal tissue compared to brain tissue suggesting an important tissue-specific role for DDAH2 in the retina and choroid. ADMA and L-NMMA levels were similar in the retina and choroid under physiological conditions. Next, characterization of DDAH1 +/− and DDAH2 −/− deficient mice by in vivo fluorescein angiography, immunohistochemistry and electroretinography revealed normal neurovascular function compared with wildtype control mice. Finally, DDAH1 +/− and DDAH2 −/− deficient mice were studied in the oxygen-induced retinopathy (OIR) model, a model used to emulate retinal ischemia and neovascularization, and VEGF and ADMA levels were quantified by ELISA and liquid chromatography tandem mass spectrometry. In the OIR model, DDAH1 +/− exhibited a similar phenotype compared to wildtype controls. DDAH2 deficiency, in contrast, resulted in elevated retinal ADMA which was associated with attenuated aberrant angiogenesis and improved vascular regeneration in a VEGF independent manner. Taken together this study suggests, that in retinal ischemia, DDAH2 deficiency elevates ADMA, promotes vascular regeneration and protects against aberrant angiogenesis. Therapeutic inhibition of DDAH2 may therefore offer a potential therapeutic strategy to protect sight by promoting retinal vascular regeneration and preventing pathological angiogenesis. Highlights: Nitric oxide has been implicated in neovascular eye disease. Key inhibitor of NO production is ADMA, which is metabolized by DDAH. DDAH2 deficiency results in elevated ADMA and reduced neovascularization in mice. Therapeutic inhibition of ADMA or DDAH2 may offer a potential therapeutic strategy.